Jaringan Syaraf Tiruan Memprediksi Jumlah Kebutuhan Air Bersih di Kota Binjai Menggunakan Metode Backpropagation (Studi Kasus : PDAM Tirta Sari Binjai) - Nico Kurniawan Purba; Rusmin Saragih; Nurhayati Nurhayati (UIN Sumatera Utara, 2021)
Water as one of the main needs to support human life and is one of the natural resources that has a very important function and is an important component of the environment for the survival of humans and other living things. Along with the increasing rate of population growth, the need for clean water also increases, so the amount of water produced continuously shows an increase in line with the increasing demand for clean water in the community. . Therefore, it is necessary to make adjustments between the supply of clean water production and the demand or need for water to consumers. Based on these conditions, PDAM Tirta Sari Binjai needs to create a system that can predict the amount of clean water needs that will come in the following days or months. The prediction results can be used to anticipate the water needs required by customers. The process of predicting the amount of clean water needed by the customer can be done with a computerized system, one of the processes that can be done is the application of an Artificial Neural Network (ANN) using the Backpropagation method. Forecasting results will be very useful for PDAM Tirta Sari Binjai in the future, because the amount of water production is the main factor in water distribution services. The system is designed with the MATLAB R2014a programming application, after carrying out the data training process and data testing on 2016 to 2020 data, the learning rate is 0.2; the maximun epoch is 10000 and the target error is 0.001, the result is that in 2020 the total need for clean water is 342,417,081 liters of water. Keywords: Backpropagation, Artificial_Syaraf_Network, Clean_Air.